Multipurpose Drugs Active Against Both Plasmodium spp. and Microorganisms: Potential Application for New Drug Development - Endo, Takuro; Takemae, Hitoshi; Sharma, Indu; Furuya, Tetsuya (Frontiers in cellular and infection microbiology, 2021)
Malaria, a disease caused by the protozoan parasites Plasmodium spp., is still causing serious problems in endemic regions in the world. Although the WHO recommends artemisinin combination therapies for the treatment of malaria patients, the emergence of artemisinin-resistant parasites has become a serious issue and underscores the need for the development of new antimalarial drugs. On the other hand, new and re-emergences of infectious diseases, such as the influenza pandemic, Ebola virus disease, and COVID-19, are urging the world to develop effective chemotherapeutic agents against the causative viruses, which are not achieved to the desired level yet. In this review article, we describe existing drugs which are active against both Plasmodium spp. and microorganisms including viruses, bacteria, and fungi. We also focus on the current knowledge about the mechanism of actions of these drugs. Our major aims of this article are to describe examples of drugs that kill both Plasmodium parasites and other microbes and to provide valuable information to help find new ideas for developing novel drugs, rather than merely augmenting already existing drug repurposing efforts.